2017
DOI: 10.21003/ea.v166-19
|View full text |Cite
|
Sign up to set email alerts
|

Youth satisfaction with the employment: a survey

Abstract: Socialization is unalienable from the economic growth thus precluding management of the social interactions within economic activities. The purpose of the research is to find out whether social factors prevail among other factors in contemporary development of the youth-oriented values to create the basis for effective human capital management. With this regard, a survey was conducted among 253 employees aged 18-29 at the 54 enterprises of different sectors in Chernivtsi region of Ukraine in December, 2015 aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Onkelinx et al (2016) find that firm-level investments in employee human capital are critical for the labor productivity and internationalization in fast internationalizes, but not for those SMEs firms that internationalize more slowly. Petrashchak et al (2017) studied factors, influencing behavior of the employees towards productivity, which are: employment stability; financial rewards; comfortable working environment; favorable working conditions and professional development. The authors found out also mistakes to the motivational stimuli as for example: exaggeration of the influence of such factors as discipline control, professional development on the job activity evaluation and the underestimation of such factors as job stability, pay rate increase (Hakelová et al, 2013).…”
Section: Present State Of Problem Solvingmentioning
confidence: 99%
“…Onkelinx et al (2016) find that firm-level investments in employee human capital are critical for the labor productivity and internationalization in fast internationalizes, but not for those SMEs firms that internationalize more slowly. Petrashchak et al (2017) studied factors, influencing behavior of the employees towards productivity, which are: employment stability; financial rewards; comfortable working environment; favorable working conditions and professional development. The authors found out also mistakes to the motivational stimuli as for example: exaggeration of the influence of such factors as discipline control, professional development on the job activity evaluation and the underestimation of such factors as job stability, pay rate increase (Hakelová et al, 2013).…”
Section: Present State Of Problem Solvingmentioning
confidence: 99%
“…The survey by O. Petrashchak, I. Kolosinskyi, M. Kolosinska, V. Marych (2017) shows that such factors as job stability, pay rate increase are underestimation [25].…”
Section: Introductionmentioning
confidence: 99%